Innovating Business Models in Times of Accelerated Change (GESTIÓN Y TENDENCIAS, 2019)
The fourth industrial revolution poses new challenges for organizations seeking to consolidate their position in the markets where they offer their products or services, or else to expand into new markets beyond their borders. Global competition takes place in a very different setting from that of the end of the last century. Advances in artificial intelligence, 3D design, big data, robotics, and cybersecurity, together with the consolidation of market trends such as the efficient use of natural resources and the incorporation of environmentally friendly technologies, have forced organizations to rethink their corporate strategies, moving from traditional models (Porter's cost leadership) toward perspectives in which innovation plays a leading role.